3D finite element model for hybrid FRP-confined concrete in compression using modified CDPM - Ribeiro, Filipe (2019)
The main goal of the work herein presented is to propose an accurate three-dimensional finite element model to predict the compressive behaviour of hybrid FRP-confined concrete. This was achieved through the modification of the concrete damaged plasticity model (CDPM) available in ABAQUS software, since the original CDPM has shortcomings that make it unusable to predict the compressive behaviour of confined concrete. It was demonstrated that, by turning the yield function and the flow rule dependents on the confining pressure, it is possible to use the model referred to and obtain accurate results. An analytical model was used to obtain the input parameters needed to calibrate the CDPM. A specific user subroutine was developed to modify the original CDPM. Hybrid FRP properties were calibrated as well, using an appropriate analytical model. Plasticity was assumed in the hybrid combinations for which pseudo-ductile tensile responses occurred. The performance of the proposed CDPM was validated using both experimental results and analytical predictions. It was concluded that, by using the developed 3D finite element model for hybrid FRP-confined concrete in compression, a very good agreement between experimental, analytical and numerical compressive stress-strain and lateral strain-axial strain curves is reached.